How Do Metal Ion Levels Change over Time in Hip Resurfacing Patients? A Cohort Study. (14th December 2014) - Savarino, Lucia; Cadossi, Matteo; Chiarello, Eugenio; Fotia, Caterina; Greco, Michelina; Baldini, Nicola; Giannini, Sandro
Abstract : Metal-on-metal hip resurfacing (MOM-HR) is offered as an alternative to traditional hip arthroplasty for young, active adults with advanced osteoarthritis. Nevertheless, concerns remain regarding wear and corrosion of the bearing surfaces and the resulting increase in metal ion levels. We evaluated three cohorts of patients with Birmingham hip resurfacing (BHR) at an average follow-up of 2, 5, and 9 years. We asked whether there would be differences in ion levels between the cohorts and inside the gender. Nineteen patients were prospectively analyzed. The correlation with clinical-radiographic data was also performed. Chromium, cobalt, nickel, and molybdenum concentrations were measured by atomic absorption spectrophotometry. Chromium and cobalt levels demonstrated a tendency to decrease over time. Such tendency was present only in females. An inverse correlation between chromium, implant size, and Harris hip score was present at short term; it disappeared over time together with the decreased ion levels. The prospective analysis showed that, although metal ion levels remained fairly constant within each patient, there was a relatively large variation between subjects, so mean data in this scenario must be interpreted with caution. The chronic high exposure should be carefully considered during implant selection, particularly in young subjects, and a stricter monitoring is mandatory.